2021
DOI: 10.1111/cpr.13007
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomes of mouse bladder urothelium uncover novel cell type markers and urothelial differentiation characteristics

Abstract: Objectives Much of the information to date in terms of subtypes and function of bladder urothelial cells were derived from anatomical location or by the expression of a small number of marker genes. To have a comprehensive map of the cellular anatomy of bladder urothelial cells, we performed single‐cell RNA sequencing to thoroughly characterize mouse bladder urothelium. Materials and methods A total of 18,917 single cells from mouse bladder urothelium were analysed by unbiased single‐cell RNA sequencing. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
(132 reference statements)
1
17
0
Order By: Relevance
“… 40 Intriguingly, trajectory analysis of urothelial cells would often be disrupted by a large number of ribosomal genes which also developed pseudotime properties in some datasets. This observation was also seen in a previous study, about 90% of top pseudotime genes were located in ribosomes, 9 yet the remaining genes (Gstm1, Tmsb4x, S100a6, and Malat1) were still aligned with our study. This phenomenon might imply that the urothelial cells may have been more heavily damaged during the sample preparation because of their exposure as the outermost layer or their intolerance and sensitivity to cell digestive agents (multiple enzymes).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 40 Intriguingly, trajectory analysis of urothelial cells would often be disrupted by a large number of ribosomal genes which also developed pseudotime properties in some datasets. This observation was also seen in a previous study, about 90% of top pseudotime genes were located in ribosomes, 9 yet the remaining genes (Gstm1, Tmsb4x, S100a6, and Malat1) were still aligned with our study. This phenomenon might imply that the urothelial cells may have been more heavily damaged during the sample preparation because of their exposure as the outermost layer or their intolerance and sensitivity to cell digestive agents (multiple enzymes).…”
Section: Discussionsupporting
confidence: 92%
“…Yu et al 8 have reported an admirable study sketching a single‐cell transcriptomic map of bladder in both mouse and human, but this research is entirely lacking any cell‐cell interaction analysis. Li et al 9 have demonstrated a novel cell type labeled by Plxna4 using scRNA‐seq in the mouse bladder, but this study is only focusing on the urothelial layer and without cell communicative network analysis or validation of any human samples. Studies have suggested that cross talk between cells profoundly impacts the development and the regeneration of the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, female C57BL/6 mice urothelial cells were analyzed and classified into eight clusters dependent on expression of cell-specific markers. A novel urothelial cell type expressing Plxna4 was discovered in the mouse bladder ( Li et al., 2021 ) which is conserved in humans and may play a role in host immune response ( Wen et al., 2010 ).…”
Section: Animal Models For Studying Utimentioning
confidence: 99%
“…Louvain clustering was performed on the gene features of scRNA-seq data collected from human lymphocytes, mouse bladder, mouse kidney, hydra, or planaria (Figure 1, S1) [Blondel 2008, Zheng 2017, Li 2021, Park 2018, Siebert 2019, Fincher 2018. Louvain clustering was performed on each sample independently, and across these samples we observed three general expression patterns: 1) A group of genes that are nearly ubiquitously expressed across all cells.…”
Section: Characterizing Patterns Of Gene Expression Variation Across Tissues and Multicellular Organismsmentioning
confidence: 99%
“…Using these approaches, it has been demonstrated that the HVG method only marginally improves performance compared to a randomized feature selection control ]. Yet, the HVG method remains extremely popular [Luecken 2019, Park 2018, Fincher 2018, Gerber 2018, Siebert 2019, Xi 2020, Diaz 2020, Collin 2021, Fawkner-Corbett 2021, Li 2021]. In addition to uncertainty about the ability of various methods to identify an informative set of biologically varying genes, the HVG, NBDisp, and Townes method all entail arbitrary decisions about the number of features to use in the downstream clustering procedure.…”
Section: Introductionmentioning
confidence: 99%